1988
DOI: 10.1023/a:1015913207052
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The swelling and dissolution behavior of pharmaceutical systems containing a drug and a polymer can be analyzed by a mathematical model which predicts the drug released and the gel layer thickness as a function of time. It is possible to approximate the values of several of the physicochemical parameters of this model in order to obtain an order-of-magnitude analysis of the tablet dissolution process. Selected experimental results of tablet dissolution and drug release are analyzed and conclusions are made abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(41 citation statements)
references
References 1 publication
0
41
0
Order By: Relevance
“…12,13 Mechanistically, release kinetics depend on the relative ratio of the rate of polymer swelling at the advancing glassy/rubbery front to the rate of polymer erosion/drug dissolution at the swollen polymer/dissolution front. It has been demonstrated that ideally the synchronization of the velocities of the swelling front and erosion front leads to linear release kinetics as long as the surface area through which drug is released remains constant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Mechanistically, release kinetics depend on the relative ratio of the rate of polymer swelling at the advancing glassy/rubbery front to the rate of polymer erosion/drug dissolution at the swollen polymer/dissolution front. It has been demonstrated that ideally the synchronization of the velocities of the swelling front and erosion front leads to linear release kinetics as long as the surface area through which drug is released remains constant.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that ideally the synchronization of the velocities of the swelling front and erosion front leads to linear release kinetics as long as the surface area through which drug is released remains constant. 13 This, however, does not occur in pharmaceutical dosage forms and drug delivery systems, 14 and often the fraction of drug released (M t /M ∞ ) can be expressed as a power function of time t:…”
Section: Resultsmentioning
confidence: 99%
“…The dissolution profile of all the batches was fitted to zeroorder, first-order, 11,12 Higuchi, [13][14][15] Hixon-Crowell, 16 Korsemeyer and Peppas, 10,17,18 and Weibull models [19][20][21][22] to ascertain the kinetic modeling of drug release. The method of Bamba et al was adopted for deciding the most appropriate model.…”
Section: Kinetic Modeling Of Drug Releasementioning
confidence: 99%
“…to characterize the dissolution profile [45][46][47][48][49][50][51]. The model which gave the highest coefficient of determination (R 2 ) was considered to be the most suitable kinetic model for describing the release of aceclofenac from the microspheres.…”
Section: Higuchi Equation and Korsmeyer-peppas Equation Were Selectedmentioning
confidence: 99%